Prevalence of Bacterial Conjunctivitis and Allergic Conjunctivitis in Pakistan - Nisar Ahmed Jandan, Nisar Ahmed Khan, Maqbool Ahmed Jamali, Ashfaque Ahmed Abbasi, Ateeq-Ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the prevalence of bacterial conjunctivitis and allergic conjunctivitis in Pakistan. Study Design: Prospective study Place and Duration of Study: Department of Ophthalmology, People Medical College Hospital Nawabshah from 1st January 2019 to 30th June 2019. Methodology: One hundred patients age between 8-15 years were enrolled depending upon their clinical symptoms of conjunctivitis. Each patient sample was then taken though conjunctival swab test and sent to laboratory for confirmation. Allergic conjunctivitis and bacterial conjunctivitis were identified with slit lamp examination, while Allergic conjunctivitis was confirmed through presence of the papillae in the upper portion of the tarsal conjunctiva correlating with the clinical symptoms of the patient. Results: The mean age of the patients was 13.3±3.4 years. The allergic conjunctivitis was observed in 18.18% of total examined cases while 12.72% had bacterial conjunctivitis. The odds ratio between boys and girls with 95% Confidence interval showed no significant variance between allergic conjunctivitis and bacterial conjunctivitis patients. Within the bacterial conjunctivitis positive cases majority of the patients suffered from staphylococcus aureus followed by hemophilic influenzae. Conclusion: Significant cases of allergic and bacterial conjunctivitis were found.